If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 + -2x = 10x + 16 Reorder the terms: 88 + -2x = 16 + 10x Solving 88 + -2x = 16 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 88 + -2x + -10x = 16 + 10x + -10x Combine like terms: -2x + -10x = -12x 88 + -12x = 16 + 10x + -10x Combine like terms: 10x + -10x = 0 88 + -12x = 16 + 0 88 + -12x = 16 Add '-88' to each side of the equation. 88 + -88 + -12x = 16 + -88 Combine like terms: 88 + -88 = 0 0 + -12x = 16 + -88 -12x = 16 + -88 Combine like terms: 16 + -88 = -72 -12x = -72 Divide each side by '-12'. x = 6 Simplifying x = 6
| (2x-9)(2x+7)=(2x-5)(2x+3) | | M-2=8 | | 6x(-9)= | | 8=x-(-1) | | 2x+26=9x-51 | | 2b+5=7 | | 12-8x=72-22x | | 3=r-14 | | -1-8x=10x+23 | | 223-6x=30x+23 | | 5x-26=34 | | 12x-33=7x+2 | | 3x+10=-67-8x | | 2(p-3)=4(p-10) | | 15v^2-19v-10= | | 114-10x=7x+22 | | 4x+10=82-4x | | 2y+5=9 | | 5x-25=20 | | 7+10=115+x | | 110-6x=3x+11 | | -16-5x=12-9x | | 4x+14=77-5x | | -2(5x-3)=-10x+11 | | 3x+25=12x-83 | | 3x+30=5x+14 | | 3x^2-4x+5=0 | | 3x-3=11x-43 | | 2x+29=12x-91 | | x^2-6=0 | | 5x-8=6x-1 | | 0=-4x-32 |